2015
DOI: 10.1371/journal.pone.0124947
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Technical Success and Rate of Complications of Image-Guided Percutaneous Transthoracic Lung Needle Biopsy of Pulmonary Tumors

Abstract: PurposeTo investigate predictors of technical success and complications of computed tomography (CT)-guided percutaneous transthoracic needle biopsy of potentially malignant pulmonary tumors.Material and MethodsFrom 2008 to 2009, technical success and rate of complications of CT-guided percutaneous transthoracic lung needle biopsies of patients with suspicious pulmonary tumors were retrospectively evaluated. The influence on technical success and rate of complications was assessed for intervention-related predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
3
19
0
3
Order By: Relevance
“…The rate of biopsy success, which was defined as providing sufficient amount of tissue for histopathologic confirmation of malignant lesion, was 93.4% in our study (93.6% in liver biopsies [US-guided], 89.7% in lung biopsies [CT-guided]). This figure is comparable or higher than those of previous studies on liver [11,12] and lung biopsies [1316]. Various studies have investigated the factors affecting biopsy success rate, and reported that selecting appropriate target lesion is one of the most important steps for a successful biopsy [8,17].…”
Section: Discussionsupporting
confidence: 71%
“…The rate of biopsy success, which was defined as providing sufficient amount of tissue for histopathologic confirmation of malignant lesion, was 93.4% in our study (93.6% in liver biopsies [US-guided], 89.7% in lung biopsies [CT-guided]). This figure is comparable or higher than those of previous studies on liver [11,12] and lung biopsies [1316]. Various studies have investigated the factors affecting biopsy success rate, and reported that selecting appropriate target lesion is one of the most important steps for a successful biopsy [8,17].…”
Section: Discussionsupporting
confidence: 71%
“…The rate of biopsy-related hemoptysis in PTNB ranged from 1.8% to 20.6% in previous studies ( 5 7 8 11 14 17 18 19 20 21 22 23 ). This wide range of hemoptysis may be attributed to the variety of biopsy methods available, operator experience, or the definition of hemoptysis among the studies ( 5 7 8 11 14 17 18 19 20 21 22 23 ). When the studies were limited to CBCT-guided PTNB, the frequency of hemoptysis was 2.0–14.5% ( 7 11 18 19 20 21 23 ).…”
Section: Discussionmentioning
confidence: 84%
“…Pneumothorax is the most frequent complication of CT-guided PTPB with a reported post-procedure incidence ranging between 17–60% [ 6 , 16 , 17 ]. A chest tube placement for pneumothorax therapy is needed in 1%-14% of cases [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided PTPB is known to be less risk entailing for the patient compared to surgical procedures, as it is less invasive and still provides a high diagnostic accuracy. The most frequent complication after PTPB is the occurrence of a pneumothorax, which has an incidence of up to 50–60% after PTPB [ 1 6 ] and can lead to a considerable reduction in the health state of the patient and longer hospitalization [ 7 ].…”
Section: Introductionmentioning
confidence: 99%